Karakteristik Habitat Tumbuhan Inang (Tetrastigma) Rafflesia meijeri di Taman Nasional Batang Resor 7 Sopotinjak Mandailing Natal Sumatera Utara: Habitat Characteristics of the Host Plant (Tetrastigma) Rafflesia meijeri in Batang Gadis National Park Sopotinjak Resor 7 Mandailing Natal Regency North Sumatra - Siti Rohimah; Viny Volcherina Darlis; Niskan Walid Masruri (JURNAL HUTAN TROPIKA, 2026)
This study aims to (1) determine the biotic factors of the host plant habitat in the Rafflesia meijeri habitat in Batang Gadis National Park, Resort 7 Sopotinjak, Mandailing Natal Regency, North Sumatra, (2) to determine the abiotic factors of the host plant habitat in the Rafflesia meijeri habitat in Batang Gadis National Park, Resort 7 Sopotinjak, Mandailing Natal Regency, North Sumatra. The research was conducted using a quantitative descriptive method through a vegetation ecology approach and specific habitat studies.Plot determination used a purposive sampling method. The observed parameters included biotic factors such as the condition of the host plant, the condition of Rafflesia meijeri, and the surrounding vegetation. Abiotic factors included temperature, air humidity, light intensity, altitude, slope, rainfall, and soil characteristics. The research results showed that the host plant of Rafflesia meijeri is Tetrastigma papillosum, which climbs the Castanopsis javanica tree. Seventeen individuals of Rafflesia meijeri were found. The dominant vegetation at the seedling and understory levels is Saurauia pendula, while at the sapling to tree level it is dominated by Syzygium racemosum and Ilex micrococca. The habitat environmental conditions have a temperature of 21.1–22.8 °C, air humidity of 76.1–77%, light intensity of 674–848 lux, an altitude of 1263–1285 meters above sea level, and Soil types are cambisol and andosol, granular-platy soil structure, clay, clay loam soil texture, reddish black-very dusky red soil color and soil pH 6.73-6.98. The characteristics of this habitat indicate humid, shady, and stable environmental conditions that support the growth of host plants and the development of Rafflesia meijeri.